S221. THE EFFICACY OF LUMATEPERONE 42 MG IN THE TREATMENT OF SCHIZOPHRENIA SYMPTOMS ASSOCIATED WITH SOCIAL FUNCTIONING: POST HOC ANALYSIS OF AN ACUTE PLACEBO- AND ACTIVE-CONTROLLED TRIAL. (18th May 2020) - Vanover, Kimberly; Davis, Robert; Durgam, Suresh; Huo, Jason; Mates, Sharon; Satlin, Andrew; Harvey, Philip D
Abstract: Background: Deficits in social functioning are a core feature of schizophrenia and may be due to the interaction of multiple factors including negative symptoms, depression symptoms, and deficits in social cognition. Social and functional impairment in schizophrenia can be difficult to treat, may not correlate with improvements in psychotic symptoms, and has been associated with poor long-term patient outcomes. Lumateperone (lumateperone tosylate, ITI-007) is a mechanistically novel agent for the treatment of schizophrenia that simultaneously modulates serotonin, dopamine, and glutamate neurotransmission. Lumateperone was shown to be efficacious and well tolerated in 2 acute placebo-controlled studies and its safety and effectiveness was further supported in a long-term open-label study. The effects of lumateperone 42 mg (ITI-007 60 mg) on schizophrenia symptoms associated with social function were investigated in a post hoc analysis of a study that included risperidone 4 mg as an active control (Study 005, NCT01499563). Symptoms associated with social functioning were assessed with the Positive and Negative Syndrome Scale (PANSS)-derived Prosocial factor (PANSS items P3, P6, N2, N4, N7, G16), which has been utilized previously to evaluate the efficacy of various antipsychotics on this functional domain. Methods: This is a post hoc analysis of data from a positive placebo- and active-controlled study in patients with an acute exacerbation of schizophrenia. Change from baseline in the PANSS Prosocial factor was assessed in the intent-to-treat (ITT) population and in patients with prominent negative symptoms (PNS, score ≥4 on at least 3 negative symptom items) or moderate-to-severe depression symptoms (Calgary Depression Scale for Schizophrenia [CDSS] ≥6) at baseline. Inferential analysis was conducted using a mixed-effects model for repeated measures (MMRM). Results: The ITT population comprised 231 patients (placebo, n=80; lumateperone 42 mg, n=76; risperidone 4 mg, n=75); the PNS and CDSS ≥6 populations comprised 110 and 54 patients, respectively. Lumateperone 42-mg treatment was associated with significantly greater improvement compared with placebo on the PANSS Prosocial factor (least-squares mean difference [LSMD] vs placebo = −2.7; P<.001). Risperidone also was superior to placebo on the PANSS Prosocial factor (LSMD= −1.8; P=.011). Similar treatment effects for lumateperone 42 mg were seen on the PANSS Prosocial factor in patients with PNS at baseline (LSMD −2.6, P=.006). Conversely, in patients with PNS, risperidone treatment showed small and non-significant treatment effects on the PANSS Prosocial factor (LSMD= −0.4; P=.707). In patients with moderate-to-severe depression symptoms at baseline, marked and significant improvements on the PANSS Prosocial factor were seen in lumateperone-treated patients (LSMD= −4.9; P<.001) but not in risperidone-treated patients (LSMD=−1.3; P=.397). Discussion: Lumateperone 42 mg significantly improved schizophrenia symptoms related to social functioning. In contrast to risperidone, lumateperone was associated with similar or greater treatment effects on the PANSS Prosocial factor in patients with prominent negative symptoms or moderate-to-severe depression symptoms at baseline. These results suggest that lumateperone may have benefits on schizophrenia symptoms associated with social function.